Protein substitute dosage in PKU: how much do young patients need?. Issue 7 (17th March 2006) - MacDonald, A; Chakrapani, A; Hendriksz, C; Daly, A; Davies, P; Asplin, D; Hall, K; Booth, I W
Abstract : Background: The optimal dose of protein substitute has not been determined in children with phenylketonuria (PKU). Aim: To determine if a lower dose of protein substitute could achieve the same or better degree of blood phenylalanine control when compared to the dosage recommended by the UK MRC. 1 Methods: In a six week randomised, crossover study, two doses of protein substitute (Protocol A: 2 g/kg/day of protein equivalent; Protocol B: 1.2 g/kg/day protein equivalent) were compared in 25 children with well controlled PKU aged 2–10 years (median 6 years). Each dose of protein substitute was taken for 14 days, with a 14 day washout period in between. Twice daily blood samples (fasting pre-breakfast and evening, at standard times) for plasma phenylalanine were taken on day 8–14 of each protocol. The median usual dose of protein substitute was 2.2 g/kg/day (range 1.5–3.1 g/kg/day). Results: When compared with control values, median plasma phenylalanine on the low dose of protein substitute increased at pre-breakfast by 301 μmol/l (95% CI 215 to 386) and in the evening by 337 μmol/l (95% CI 248 to 431). On the high dose of protein substitute, plasma phenylalanine concentrations remained unchanged when compared to control values. However, wide variability was seen between subjects. Conclusions: A higher dosage of protein substitute appeared to contribute to lower blood phenylalanine concentrations in PKU, but it did have a variable and individual impact and may have been influenced by the carbohydrate (+/− fat) content of the protein substitute.